2016
DOI: 10.1126/sciadv.1501851
|View full text |Cite
|
Sign up to set email alerts
|

Metadisorder for designer light in random systems

Abstract: We propose the concept of metadisorder for globally collective and small-world–like waves in randomly coupled systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…1. It is a popular model studied in the optics community, among others, where it is used to understand how the introduction of disorder in lattices influences the resultant optical properties of the materials [3,4,[22][23][24][25][26][27][28][29][30]. Perturbed lattices are special cases of hyperuniform systems.…”
Section: Introductionmentioning
confidence: 99%
“…1. It is a popular model studied in the optics community, among others, where it is used to understand how the introduction of disorder in lattices influences the resultant optical properties of the materials [3,4,[22][23][24][25][26][27][28][29][30]. Perturbed lattices are special cases of hyperuniform systems.…”
Section: Introductionmentioning
confidence: 99%
“…Our new findings of low-dimensional chirality will pave a route toward active chiral devices [25], such as on-chip guided-wave devices for chiral lasers, amplifiers, absorbers, and switches [34] as well as complex chiral metamaterials [9] and topological phases. From the evident correlation between complex potentials and optical chirality, we can also imagine the eigenstate with nontrivial optical spins in 'non-PT-symmetric' complex potentials, by utilizing supersymmetry technique [35,36] or the inverse design of an eigenstate in disordered media [37]. Based on the general framework of non-Hermitian physics, we note that our work can be further extended using different polarization bases (Supplementary Note 6) to enable SOP collection for the arbitrary designer polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The task of driving light at the nanoscale is usually fulfilled by homogeneous waveguides or photonic crystals supporting a band gap [4]: completely ordered structures which allow to tailor the light flow. On the other hand, recent studies on complex materials and photonic glasses [5,6] demonstrated that complete gaps can be found also in case of designed disorder [7,8], which is today inspiring new platforms to overcome the present limitations encountered in photonic applications [9] and enabling extraordinary optical phenomena [10][11][12][13]. Light propagating in disordered media generates speckle patterns that are also complex light features, they are originated by random scattering through or by a rough dielectric slab.…”
Section: Introductionmentioning
confidence: 99%